Effect of Different Organic Fertilizers and NPK on Growth and Yield of Lentil (Lens culinaris) - K.C., Pramod; Sharma, Raksha; Karki, Ramesh Bahadur; Joshi, Naresh; Bogati, Durga; Timilsina, Kusum; Bhatta, Pramod; Dangi , Prabin; K.C., Susmita (Agronomy Journal of Nepal, 2024)
The experiment was conducted during the month of November, 2022-March, 2023 in Agronomy Farm, Department of Agriculture, Far Western University, Tikapur, Kailali, Nepal to evaluate the combine effects of different organic fertilizers and NPK on growth and yield attributes of lentils. The experiment was laid out in a randomized complete block design (RCBD) with four treatments and five replications. The treatments used were: Farm yard manure @ 6 t ha-1 (T1), vermicompost @ 1 t ha-1 (T2), panchagavya @ 3% solution (T3) and control (T4). The recommended dose of chemical fertilizers (20:20:20 kg NPK ha-1) were used as a basal dose in all the treatments. It was observed that the application of FYM proved to be significantly superior in terms of plant height, branch number, first flat pod observation, number of pods/plant (107.18), number of filled pods/plant (101.30), total biomass/plant (79.0 g), number of seeds/pod (1.87) and grain yield/ha (1558 kg). The effects remain similar and non-significant in terms of parameters like germination percentage and other growth stages i.e., branching, flowering, number of unfilled pods/plant, pod weight/plant, grain weight/plant, 1000 grain weight, stover yield and harvest index. FYM also recorded the highest gross return (Rs. 155,800) and net return (Rs. 103,183.33) with a slightly lower BC ratio (2.96) compared to control (3.12). In conclusion, FYM proved to be the best option for achieving the highest grain yield and overall economic returns while control remained the most economical choice based on the benefit-cost ratio.